Synthesis, Characterization and Biological Evaluation of Some Dihydropyrimidinones - Vijay, K.; Ganapaty, S.; Srinivas Rao, A. (Asian Journal of Chemistry, 2010)
An efficient and facile one pot synthesis of 3,4-dihydropyrimidinones (Biginelli compounds) from divergent aldehydes, β-keto esters and urea or thiourea under solvent free conditions was performed using citric acid as catalyst, resulted in promising yields. These compounds were subjected for anticancer and antiinflammatory activities which showed significant activities.